EXPERIMENTAL INVESTIGATION OF ZOISITE-CLINOZOISITE PHASE EQUILIBRIA IN THE SYSTEM CAO-FE2O3-AL2O3-SIO2-H2O - Brunsmann A.; Franz G.; Heinrich W. (My University, 2002)
The system Ca2Al3Si3O11(O/OH)-Ca2Al2FeSi3O11(O/OH), with emphasis on the Al-rich portion, was investigated by synthesis experiments at 0.5 and 2.0 GPa, 500-800 °C, using the technique of producing overgrowths on natural seed crystals. Electron microprobe analyses of overgrowths up to >100 µm wide have located the phase transition from clinozoisite to zoisite as a function of P-T-Xps and a miscibility gap in the clinozoisite solid solution. The experiments confirm a narrow, steep zoisite-clinozoisite two-phase loop in T-Xps section. Maximum and minimum iron contents in coexisting zoisite and clinozoisite are given by $${\rm X}_{{\rm ps}}^{{\rm zo}} {\rm (max) = 1}{\rm.9*10}^{ - 4} T{\rm + 3}{\rm.1*10}^{ - 2} P - {\rm 5}{\rm.36*10}^{ - 2} $$ and $${\rm X}_{{\rm ps}}^{{\rm czo}} {\rm (min)} = {\rm (4}{\rm.6} * {\rm 10}^{ - {\rm 4}} - 4 * {\rm 10}^{ - {\rm 5}} P{\rm )}T + {\rm 3}{\rm.82} * {\rm 10}^{ - {\rm 2}} P - {\rm 8}{\rm.76} * {\rm 10}^{ - {\rm 2}} $$ (P in GPa, T in °C). The iron-free end member reaction clinozoisite = zoisite has equilibrium temperatures of 185±50 °C at 0.5 GPa and 0±50 °C at 2.0 GPa, with ΔHr0=2.8±1.3 kJ/mol and ΔSr0=4.5±1.4 J/mol×K. At 0.5 GPa, two clinozoisite modifications exist, which have compositions of clinozoisite I ~0.15 to 0.25 Xps and clinozoisite II >0.55 Xps. The upper thermal stability of clinozoisite I at 0.5 GPa lies slightly above 600 °C, whereas Fe-rich clinozoisite II is stable at 650 °C. The schematic phase relations between epidote minerals, grossular-andradite solid solutions and other phases in the system CaO-Al2O3-Fe2O3-SiO2-H2O are shown.